EMPATHY DEVELOPMENT WITH ACTIVE LEARNING FOR STUDENTS IN CLASS V ELEMENTARY SCHOOL - Nurhasanah, Nina; Zulela, Zulela; Solihatin, Etin (Universitas Ahmad Dahlan, 2020)
The research aims to know the learning process with active learning in developing empathy for class V students in elementary school. There are two research participants: SD Laboratory of PGSD FIP UNJ and SD Budi Wanita in Setiabudi Jakarta Indonesia. Research methods use a naturalistic qualitative method. The data collection process is doing by observation, interviews, and document analysis. The observation results analyzed by focused observation, taxonomy analysis, selected observation, component analysis, and theme analysis. The validity of the data is doing by extension of participation, the persistence of observation, and triangulation. The findings suggest that grade V students in elementary school have been able to develop empathy. The strategies that teachers do in active learning to develop empathy in the form of role-playing, Jigsaw, discussion, group work, and use games performed on early activities, core activities, and end-of-learning activities. Using active learning in learning in class V in elementary school can develop students ' empathy.